Kritik terhadap Fenomena Literasi Tanpa Iman: Analisis Pendidikan Islam Kontemporer dalam Perspektif Hadis Nabawi - Ahmad Taupik; Achmad Affandy (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Contemporary Islamic education faces a crisis of value transformation, where cognitive literacy achievements do not correspond proportionally to the quality of moral conduct (adab) and spiritual internalization. This study aims to examine this failure through a critical review of Prophetic Hadith on the phenomenon of literacy without faith. Employing a qualitative descriptive method based on library research, it analyzes relevant Hadith literature, books, and journals. The findings reveal that modern educational practices tend to reverse the learning sequence by prioritizing textual mastery before instilling the foundations of faith. This indicates that curricular formalism may impede the inner transformation of learners. The novelty of this research lies in its methodological critique of educational orientations that place text above faith. The study concludes that restoring the Prophetic method, guided by the principle of